2017
DOI: 10.1002/uog.17494
|View full text |Cite
|
Sign up to set email alerts
|

Placental histopathology associated with pre‐eclampsia: systematic review and meta‐analysis

Abstract: Objective Pre-eclampsia (PE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
89
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 25 publications
10
89
0
2
Order By: Relevance
“…More recent data have shown that abnormal placentation is neither specific for nor sensitive to the occurrence of preeclampsia, even though placental lesions are seen more frequently in early preeclampsia (Falco et al . ). Today, evidence is growing that pre‐existing or early pregnancy suboptimal cardiac dysfunction may predispose to subsequent placental maldevelopment (Mahendru et al .…”
Section: Cardiorenal Interactions In the Pathophysiology Of Preeclampsiamentioning
confidence: 97%
See 1 more Smart Citation
“…More recent data have shown that abnormal placentation is neither specific for nor sensitive to the occurrence of preeclampsia, even though placental lesions are seen more frequently in early preeclampsia (Falco et al . ). Today, evidence is growing that pre‐existing or early pregnancy suboptimal cardiac dysfunction may predispose to subsequent placental maldevelopment (Mahendru et al .…”
Section: Cardiorenal Interactions In the Pathophysiology Of Preeclampsiamentioning
confidence: 97%
“…Similarly, the acute nature of the cardiovascular insult resulting in hypoperfusion of the placenta is short‐lived and unlikely to result in histologically evident placental damage (Falco et al . ). The links between cardiac and renal dysfunction in this process are comparable to those involved in early‐onset preeclampsia; however, venous congestion dominates over arterial hypoperfusion and reflex hypertonia, due to which the clinical presentation of this type of preeclampsia, is less fulminant and usually in a later stage of pregnancy.…”
Section: Cardiorenal Interactions In the Pathophysiology Of Preeclampsiamentioning
confidence: 97%
“…We thank Orabona et al . for their comments on our paper in which it was demonstrated that villous and vascular placental lesions are found more frequently in pre‐eclamptic pregnancies. The authors had previously shown that the incidence of similar placental lesions in pre‐eclampsia was different according to gestational age at pre‐eclampsia onset, with lesions being more prevalent in early‐onset disease.…”
mentioning
confidence: 87%
“…Instead of trying to change clinical diagnostic criteria, we would ask Orabona and colleagues to consider the etiological implications of the findings of both studies. The chronological order of findings (abnormal uterine artery Doppler indices at 12–20 weeks' gestation precedes placental lesions in pre‐eclampsia developing later in pregnancy) would suggest that abnormal uterine flow causes placental lesions, and not vice versa .…”
mentioning
confidence: 99%
“…Falco et al . conducted a systematic review and meta‐analysis in order to quantify the prevalence of placental villous and vascular histopathological lesions in pregnancies complicated by pre‐eclampsia (PE).…”
mentioning
confidence: 99%